Grounded Identities : Territory and Belonging in the Medieval and Early Modern Middle East and Mediterranean - Tamari, Steve, (Middle East and Islamic Studies E-Books Online, Collection 2019, ISBN: 9789004386341., 2019)
Grounded Identities: Territory and Belonging in the Medieval and Early Modern Middle East and Mediterranean is a collection of essays on attachment to specific lands including Kurdistan, Andalusia and the Maghrib, and geographical Syria in the pre-modern Islamicate world. Together these essays put a premium on the affective and cultural dimensions of such attachments, fluctuations in the meaning and significance of lands in the face of historical transformations and, at the same time, the real and persistent qualities of lands and human attachments to them over long periods of time. These essays demonstrate that grounded identities are persistent and never static. Contributors are: Zayde Antrim, Alexander Elinson, Mary Hoyt Halavais, Boris James, Steve Tamari.